The Role of Ahlussunnah Wal Jama'ah in Building a Moderate Islamic Civilization - Mutia Fadhilah; Achmad Maftuh Sujana; Dian Kartika; Haliza Alifia Ifada; Ahmad Lathif (Edusoshum : Journal of Islamic Education and Social Humanities, 2025)
The development of socio-religious dynamics in Indonesia today faces the challenge of polarization between religious radicalism and liberalism that has the potential to undermine the foundations of moderate Islam. This research aims to comprehensively describe the strategic role of Ahlussunnah wal Jama'ah (Aswaja) in building a moderate Islamic civilization through theological, institutional, and cultural pillars. The method used is a qualitative approach with an analytical descriptive design, which utilizes content analysis techniques against credible national and international scientific literature in the last ten years. The results of the study show that Aswaja functions as a theological instrument through the principles  of tawasuth, tawazun, i'tidal, and tasamuh which are filters for extreme ideologies. Institutionally, Aswaja values are transformed into habitus in Islamic boarding schools and universities to ensure inclusive social behavior. In conclusion, the cultural flexibility of Aswaja through the rules of al-muhafadzah 'ala al-qadim as-shalih allows Islam to remain relevant in the face of digital disruption and the post-truth era. The sustainability of moderate civilization is highly dependent on the resilience of the thinking methodology (manhaj al-fikr) and the strategy of digitizing Aswaja values in the future